1993
DOI: 10.1128/mcb.13.9.5290
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of c-Src activity by C-terminal Src kinase involves the c-Src SH2 and SH3 domains: analysis with Saccharomyces cerevisiae.

Abstract: The kinase activity of c-Src is normally repressed in vertebrate cells by extensive phosphorylation of Y-527. C-terminal Src kinase (CSK) is a candidate for the enzyme that catalyzes this phosphorylation. We have used budding yeast to study the regulation of c-Src activity by CSK in intact cells. Expression of c-Src in Saccharomyces cerevisiae, which lacks endogenous c-Src and Y-527 kinases, induces a kinase-dependent growth inhibition. Coexpression of CSK in these cells results in phosphorylation of c-Src on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 46 publications
7
94
0
Order By: Relevance
“…SFK proteins range in molecular mass from 52 to 62 kDa and share a conserved domain structure consisting of consecutive SH4 domain, unique domain, SH3 domain, SH2-SH3 linker, SH2 domain, SH1 (catalytic domain), and C terminal negative regulatory region. The SH3 domain contributes to substrate recruitment [110,111] and is critical for the regulation of kinase activity [112][113][114], (Fig. 4).…”
Section: Src Family Of Kinases (Sfk)mentioning
confidence: 99%
“…SFK proteins range in molecular mass from 52 to 62 kDa and share a conserved domain structure consisting of consecutive SH4 domain, unique domain, SH3 domain, SH2-SH3 linker, SH2 domain, SH1 (catalytic domain), and C terminal negative regulatory region. The SH3 domain contributes to substrate recruitment [110,111] and is critical for the regulation of kinase activity [112][113][114], (Fig. 4).…”
Section: Src Family Of Kinases (Sfk)mentioning
confidence: 99%
“…The SH2 domains of Src kinases bind their C-terminally phosphorylated tails (3-7), and this interaction stabilizes an inactive conformation. Genetic experiments first suggested that the SH3 domain of Src was also involved in the repression of catalytic activity (15,16). The three-dimensional structures of c-Src and Hck (17)(18)(19) provide an explanation for the involvement of the Src homology domains in enzyme inhibition (Fig.…”
mentioning
confidence: 99%
“…SH3 domains have been reported to act and interact intramolecularly and to be masked until activation exposes them for interaction with a target protein (Murphy et al, 1993;Okada et ai., 1993;Superti-Furga et al, 1993). Indeed, the myr 3 tail region exhibits proline-rich sequences that could possibly interact with the SH3 domain.…”
Section: Discussionmentioning
confidence: 99%